A Review of Remote Sensing and GIS based Change Detection Techniques for Identification of Sites need Ecological Restoration in Garhwal Himalayas - Singh, Ranjeet; Kumar, Parmanand (Indian Forester, 2022)
Forest ecological restoration is a vital step for climate change mitigation and maintaining biodiversity. It aims to recreate, initiate, or accelerate the recovery of an ecosystem that has been disturbed. However, forest monitoring and assessment of forest losses in the Himalayan region is a major challenge due to difficult terrain conditions. The recent advancements in Remote Sensing and Geographic Information System (RS&GIS) techniques are enabling the quick and cost-effective solution for ecological restoration by mapping, monitoring, and quantification of areas that are affected due to degradation and deforestation. The present study aims to provide a review of recent advances in the methods and data products that can be used to extract information with regard to location, timing, and extent of vegetation losses and the past studies related to vegetation change conducted in the Garhwal region of Western Himalaya. The challenges and opportunities for the use of remote sensing in the field of restoration ecology have been discussed. The review revealed that there is very limited information available about the complex Himalayan ecosystem. Further research in the field of forest monitoring to assist in early detection of degradation and formulation of area-specific ecological restoration techniques is needed.